2021
DOI: 10.21203/rs.3.rs-154835/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Increased primary carnitine deficiency detection through second-tier newborn genetic screening

Abstract: Background Newborn screening for (NBS) for primary carnitine deficiency (PCD) is widely implemented worldwide, however, with poor sensitivity. This study aimed to evaluate the feasibility of improving the screening using second-tier genetic assay. Methods An Agena iPLEX assay was developed to identify 17 SLC22A5 mutations in the Chinese populations, then this assay was applied in NBS for second-tier mutation screening of newborns with low free carnitine (C0) levels. Results The Agena iPLEX assay was success… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…NBS results showed that all patients with low C0 levels, while some patients may have normal C0 levels during recall review. These patients would have been excluded from conventional NBS, but could be identi ed by incorporating second-tier genetic screening [19]. However, it is noteworthy that PCD patients are also easily missed during NBS because the C0 levels at birth could be affected by the maternal concentration and therefore cannot re ect the true levels of the newborns themselves.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…NBS results showed that all patients with low C0 levels, while some patients may have normal C0 levels during recall review. These patients would have been excluded from conventional NBS, but could be identi ed by incorporating second-tier genetic screening [19]. However, it is noteworthy that PCD patients are also easily missed during NBS because the C0 levels at birth could be affected by the maternal concentration and therefore cannot re ect the true levels of the newborns themselves.…”
Section: Discussionmentioning
confidence: 99%
“…Newborns who tested positive on the second screen were referred for further genetic analysis. Between January 2017 and December 2018, a second-tier newborn genetic screening targeting 17 SLC22A5 variants was added to our NBS program [19]. Targeted next-generation sequencing (NGS) was performed as previously described [27].…”
Section: Nbs and Diagnostic Evaluationmentioning
confidence: 99%
See 2 more Smart Citations